2017
DOI: 10.5354/0719-5281.2016.44927
|View full text |Cite
|
Sign up to set email alerts
|

Hacia una estrategia de participación en y para la salud mental: escuela de monitores en salud mental comunitaria La Pintana

Abstract: El artículo presenta el desarrollo y evaluación preliminar de la iniciativa Escuela de Monitores en Salud Mental Comunitaria, iniciativa pionera implementada desde 2011 en la comuna de La Pintana de Santiago, orientada a promover la participación comunitaria en salud pública a través de la formación de monitores en salud mental comunitaria. Se describen datos preliminares relativos a tasas de graduación, adherencia a la escuela, encuestas de satisfacción y análisis FODA. Asimismo, se detallan las condiciones p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Regarding the health promoter role, the National Community Health Advisor Study identified seven core roles and competencies, highlighting cultural mediation, health education/promotion and the implementation of tangible health actions, so that the main focus of their actions is based on building a connection between community and local health systems. In this way, the "School of Communitarian Mental Health Promoters" (known in Spanish as ESMC), developed in partnership with the Communitarian Mental Health Center located in La Pintana commune (Chile), has an action range that includes prevention and intervention of mental health in the commune's territory, as well as health center decisionmaking and design/implementation of new ESMC versions (Rosenthal, 2000;Encina & Minoletti, 2016). Similarly, the "Programa de Salud de la Misión Barrio Adentro" trained communitarian health promoters in comprehensive health issues and linked them to the health center through their participation in health worker home visits, individual and group educational activities and identification of risk factors that threaten human health in the territory influenced by this program (Álvarez Sintes & Barcos Pina, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the health promoter role, the National Community Health Advisor Study identified seven core roles and competencies, highlighting cultural mediation, health education/promotion and the implementation of tangible health actions, so that the main focus of their actions is based on building a connection between community and local health systems. In this way, the "School of Communitarian Mental Health Promoters" (known in Spanish as ESMC), developed in partnership with the Communitarian Mental Health Center located in La Pintana commune (Chile), has an action range that includes prevention and intervention of mental health in the commune's territory, as well as health center decisionmaking and design/implementation of new ESMC versions (Rosenthal, 2000;Encina & Minoletti, 2016). Similarly, the "Programa de Salud de la Misión Barrio Adentro" trained communitarian health promoters in comprehensive health issues and linked them to the health center through their participation in health worker home visits, individual and group educational activities and identification of risk factors that threaten human health in the territory influenced by this program (Álvarez Sintes & Barcos Pina, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…A history of CMHWs in both countries likely contributed to participants' acceptance and comfortability with CTI-TS' task-shifting model. Chile has involved 'community health agents' (agentes comunitarios de salud) and 'community mental health monitors' (monitores de salud) for decades in rolling out its community mental health approach (Marconi, 1971;Encina and Minoletti, 2016;Ministerio de Salud, 2016). In Brazil, the community health agents (agentes comunitários de saúde) date back to 1980, and the CAPS have since incorporated and implemented many community-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The Intracommunity Psychiatry Program in the 1970s aimed to train community members together with other education and health professionals to generate a stepped system of task delegation [ 73 ]. Similar ideas have garnered renewed interest in recent years [ 74 ], converging with international strategies such as the Mental Health Global Action Programme (mhGAP) [ 75 ] for training non-specialist health personnel, which has recently expanded its scope to include lay community members [ 76 ].…”
Section: Introductionmentioning
confidence: 99%